Solve the following equations using Matrix Inversion method.
\[2x-3y+6=0\] and \[6x+y+8=0\]
Answer
Verified
442.8k+ views
Hint:To find the value of \[x\] and \[y\] we will first form a matrix from the two equation and then find the determinant of the matrix A and then we will find the inverse of matrix A and form product with a \[2\times 1\] matrix of constant value of the equation given as:
\[X={{A}^{-1}}B\]
Complete step by step solution:
The two equation given are \[2x-3y+6=0\] and \[6x+y+8=0\], and to form the matrix A we will form the matrix A as \[\left| \begin{matrix}
a & b \\
c & d \\
\end{matrix} \right|\] which is equal to \[\left| \begin{matrix}
2 & -3 \\
6 & 1 \\
\end{matrix} \right|\] and to form the matrix B we will make a \[2\times 1\] matrix of constant value of
\[\left| \begin{matrix}
m \\
n \\
\end{matrix} \right|\] as \[\left| \begin{matrix}
-6 \\
-8 \\
\end{matrix} \right|\].
With the matrix of X as \[\left| \begin{matrix}
x \\
y \\
\end{matrix} \right|\] we will form a matrix equation of:
\[\left| \begin{matrix}
x \\
y \\
\end{matrix} \right|={{A}^{-1}}\left| \begin{matrix}
m \\
n \\
\end{matrix} \right|\]
Now forming the inverse of the matrix A, we will get the inverse of matrix A as:
\[{{A}^{-1}}=\dfrac{1}{\left| A \right|}\left| \begin{matrix}
a & b \\
c & d \\
\end{matrix} \right|\]
The value of \[\left| A \right|\] is the determinant which is given as:
\[\Rightarrow \left| A \right|=\left( 2\times 1-\left( -3\times 6 \right) \right)\]
\[\Rightarrow \left| A \right|=20\]
Now with the determinant value found we will find the value of inverse matrix of A as:
\[{{A}^{-1}}=\dfrac{1}{20}\left| \begin{matrix}
1 & 3 \\
-6 & 2 \\
\end{matrix} \right|\] (The inverse of \[\left| \begin{matrix}
2 & -3 \\
6 & 1 \\
\end{matrix} \right|\] is \[\left| \begin{matrix}
1 & 3 \\
-6 & 2 \\
\end{matrix} \right|\] by interchanging the original matrix as \[\left| \begin{matrix}
d & -b \\
-c & a \\
\end{matrix} \right|\])
\[\Rightarrow {{A}^{-1}}=\dfrac{1}{20}\left| \begin{matrix}
1 & 3 \\
-6 & 2 \\
\end{matrix} \right|\]
Placing the inverse value in \[\left| \begin{matrix}
x \\
y \\
\end{matrix} \right|={{A}^{-1}}\left| \begin{matrix}
m \\
n \\
\end{matrix} \right|\] , we get:
\[\Rightarrow \left| \begin{matrix}
x \\
y \\
\end{matrix} \right|=\dfrac{1}{20}\left| \begin{matrix}
1 & 3 \\
-6 & 2 \\
\end{matrix} \right|\left| \begin{matrix}
-6 \\
-8 \\
\end{matrix} \right|\]
\[\Rightarrow \left| \begin{matrix}
x \\
y \\
\end{matrix} \right|=\dfrac{1}{20}\left| \begin{matrix}
1\times -6+3\times -8 \\
-6\times -6+2\times 8 \\
\end{matrix} \right|\]
\[\Rightarrow \left| \begin{matrix}
x \\
y \\
\end{matrix} \right|=\left| \begin{matrix}
\dfrac{1\times -6+3\times -8}{20} \\
\dfrac{-6\times -6+2\times 8}{20} \\
\end{matrix} \right|\]
\[\Rightarrow \left| \begin{matrix}
x \\
y \\
\end{matrix} \right|=\left| \begin{matrix}
\dfrac{-30}{20} \\
\dfrac{52}{20} \\
\end{matrix} \right|\]
Therefore, the value of \[x=\dfrac{-3}{2}\]and \[y=\dfrac{13}{5}\]
Note: The matrix inversion method can only work on a square matrix. We will also solve these equations by elimination method and substitution method.
\[X={{A}^{-1}}B\]
Complete step by step solution:
The two equation given are \[2x-3y+6=0\] and \[6x+y+8=0\], and to form the matrix A we will form the matrix A as \[\left| \begin{matrix}
a & b \\
c & d \\
\end{matrix} \right|\] which is equal to \[\left| \begin{matrix}
2 & -3 \\
6 & 1 \\
\end{matrix} \right|\] and to form the matrix B we will make a \[2\times 1\] matrix of constant value of
\[\left| \begin{matrix}
m \\
n \\
\end{matrix} \right|\] as \[\left| \begin{matrix}
-6 \\
-8 \\
\end{matrix} \right|\].
With the matrix of X as \[\left| \begin{matrix}
x \\
y \\
\end{matrix} \right|\] we will form a matrix equation of:
\[\left| \begin{matrix}
x \\
y \\
\end{matrix} \right|={{A}^{-1}}\left| \begin{matrix}
m \\
n \\
\end{matrix} \right|\]
Now forming the inverse of the matrix A, we will get the inverse of matrix A as:
\[{{A}^{-1}}=\dfrac{1}{\left| A \right|}\left| \begin{matrix}
a & b \\
c & d \\
\end{matrix} \right|\]
The value of \[\left| A \right|\] is the determinant which is given as:
\[\Rightarrow \left| A \right|=\left( 2\times 1-\left( -3\times 6 \right) \right)\]
\[\Rightarrow \left| A \right|=20\]
Now with the determinant value found we will find the value of inverse matrix of A as:
\[{{A}^{-1}}=\dfrac{1}{20}\left| \begin{matrix}
1 & 3 \\
-6 & 2 \\
\end{matrix} \right|\] (The inverse of \[\left| \begin{matrix}
2 & -3 \\
6 & 1 \\
\end{matrix} \right|\] is \[\left| \begin{matrix}
1 & 3 \\
-6 & 2 \\
\end{matrix} \right|\] by interchanging the original matrix as \[\left| \begin{matrix}
d & -b \\
-c & a \\
\end{matrix} \right|\])
\[\Rightarrow {{A}^{-1}}=\dfrac{1}{20}\left| \begin{matrix}
1 & 3 \\
-6 & 2 \\
\end{matrix} \right|\]
Placing the inverse value in \[\left| \begin{matrix}
x \\
y \\
\end{matrix} \right|={{A}^{-1}}\left| \begin{matrix}
m \\
n \\
\end{matrix} \right|\] , we get:
\[\Rightarrow \left| \begin{matrix}
x \\
y \\
\end{matrix} \right|=\dfrac{1}{20}\left| \begin{matrix}
1 & 3 \\
-6 & 2 \\
\end{matrix} \right|\left| \begin{matrix}
-6 \\
-8 \\
\end{matrix} \right|\]
\[\Rightarrow \left| \begin{matrix}
x \\
y \\
\end{matrix} \right|=\dfrac{1}{20}\left| \begin{matrix}
1\times -6+3\times -8 \\
-6\times -6+2\times 8 \\
\end{matrix} \right|\]
\[\Rightarrow \left| \begin{matrix}
x \\
y \\
\end{matrix} \right|=\left| \begin{matrix}
\dfrac{1\times -6+3\times -8}{20} \\
\dfrac{-6\times -6+2\times 8}{20} \\
\end{matrix} \right|\]
\[\Rightarrow \left| \begin{matrix}
x \\
y \\
\end{matrix} \right|=\left| \begin{matrix}
\dfrac{-30}{20} \\
\dfrac{52}{20} \\
\end{matrix} \right|\]
Therefore, the value of \[x=\dfrac{-3}{2}\]and \[y=\dfrac{13}{5}\]
Note: The matrix inversion method can only work on a square matrix. We will also solve these equations by elimination method and substitution method.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE